PERTANGGUNGJAWABAN PIDANA DOKTER YANG MEMALSUKAN DATA KESEHATAN PASIEN - Yuniva Yuni (Fakultas Syariah Institut Agama Islam Negeri Palu, 2022)
A doctor is not just an expert to consult when sick but must be willing to explain the patient's condition data properly and honestly. In Indonesia today, fake doctor's certificates are easy to obtain both through offline sales and online sales because doctor's certificates have a simple form so that doctors and people who are not doctors can easily make them. The purpose of this study was to determine the criminal liability and code of ethics of doctors who falsify patient data. The research method used is the normative legal research method, this method describes the problems that occur and is associated with legal theory and then is also associated with the applicable legal rules. Legal consequences for doctors who commit criminal acts if there is falsification of patient data by doctors. The legal consequences received by doctors who falsify patient health data in terms of criminal law. From a criminal perspective, what often happens is related to Article 267 paragraph (1) of the Criminal Code (making fake letters or falsifying patient data) if doctors falsify letters or data, they are punished with imprisonment for a maximum of 4 years in prison.